Tunable optical spin Hall effect in a liquid crystal microcavity. Issue 1 (December 2018) - Lekenta, Katarzyna; Król, Mateusz; Mirek, Rafał; Łempicka, Karolina; Stephan, Daniel; Mazur, Rafał; Morawiak, Przemysław; Kula, Przemysław; Piecek, Wiktor; Lagoudakis, Pavlos; Piętka, Barbara; Szczytko, Jacek
Abstract The spin Hall effect, a key enabler in the field of spintronics, underlies the capability to control spin currents over macroscopic distances. The effect was initially predicted by D'Yakonov and Perel1 and has been recently brought to the foreground by its realization in paramagnetic metals by Hirsch2 and in semiconductors3 by Sih et al. Whereas the rapid dephasing of electrons poses severe limitations to the manipulation of macroscopic spin currents, the concept of replacing fermionic charges with neutral bosons such as photons in stratified media has brought some tangible advances in terms of comparatively lossless propagation and ease of detection4–7 . These advances have led to several manifestations of the spin Hall effect with light, ranging from semiconductor microcavities8, 9 to metasurfaces10 . To date the observations have been limited to built-in effective magnetic fields that underpin the formation of spatial spin currents. Here we demonstrate external control of spin currents by modulating the splitting between transverse electric and magnetic fields in liquid crystals integrated in microcavities.